A Randomized Phase 2 Trial of Felzartamab in Antibody-Mediated Rejection. - Mayer, Katharina A.; Schrezenmeier, Eva; Diebold, Matthias; Halloran, Philip F.; Schatzl, Martina; Schranz, Sabine; Haindl, Susanne; Kasbohm, Silke; Kainz, Alexander; Eskandary, Farsad; Doberer, Konstantin; Patel, Uptal D.; et al. (New England Journal of Medicine, 2024)
BACKGROUND: Antibody-mediated rejection is a leading cause of kidney-transplant failure. The targeting of CD38 to inhibit graft injury caused by alloantibodies and natural killer (NK) cells may be a therapeutic option. METHODS: In this phase 2, double-blind, randomized, placebo-controlled trial, we assigned patients with antibody-mediated rejection that had occurred at least 180 days after transplantation to receive nine infusions of the CD38 monoclonal antibody felzartamab (at a dose of 16 mg per kilogram of body weight) or placebo for 6 months, followed by a 6-month observation period. The primary outcome was the safety and side-effect profile of felzartamab. Key secondary outcomes were renal-biopsy results at 24 and 52 weeks, donor-specific antibody levels, peripheral NK-cell counts, and donor-derived cell-free DNA levels. RESULTS: A total of 22 patients underwent randomization (11 to receive felzartamab and 11 to receive placebo). The median time from transplantation until trial inclusion was 9 years. Mild or moderate infusion reactions occurred in 8 patients in the felzartamab group. Serious adverse events occurred in 1 patient in the felzartamab group and in 4 patients in the placebo group; graft loss occurred in 1 patient in the placebo group. At week 24, resolution of morphologic antibody-mediated rejection was more frequent with felzartamab (in 9 of 11 patients [82%]) than with placebo (in 2 of 10 patients [20%]), for a difference of 62 percentage points (95% confidence interval [CI], 19 to 100) and a risk ratio of 0.23 (95% confidence interval [CI], 0.06 to 0.83). The median microvascular inflammation score was lower in the felzartamab group than in the placebo group (0 vs. 2.5), for a mean difference of -1.95 (95% CI, -2.97 to -0.92). Also lower was a molecular score reflecting the probability of antibody-mediated rejection (0.17 vs. 0.77) and the level of donor-derived cell-free DNA (0.31% vs. 0.82%). At week 52, the recurrence of antibody-mediated rejection was reported in 3 of 9 patients who had a response to felzartamab, with an increase in molecular activity and biomarker levels toward baseline levels. CONCLUSIONS: Felzartamab had acceptable safety and side-effect profiles in patients with antibody-mediated rejection. (Funded by MorphoSys and Human Immunology Biosciences; ClinicalTrials.gov number, NCT05021484; and EUDRACT number, 2021-000545-40.).
EVALuna2:568222